2020
DOI: 10.1002/ehf2.13043
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in heart failure hospitalization rate during coronavirus disease 19 pandemic outbreak

Abstract: Aims The recent coronavirus disease 19 (COVID-19) pandemic outbreak forced the adoption of restraint measures, which modified the hospital admission patterns for several diseases. The aim of the study is to investigate the rate of hospital admissions for heart failure (HF) during the early days of the COVID-19 outbreak in Italy, compared with a corresponding period during the previous year and an earlier period during the same year. Methods and results We performed a retrospective analysis on HF admissions num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 22 publications
4
43
0
Order By: Relevance
“…In this study we extended the time frame of observation reporting the data of the first trimester 2020 from a different region of Italy, i.e., the Tuscany, and we demonstrated that a low rate of contacts to EMS during this pandemic was observed also in regions of Italy less affected by the pandemic. We found that the reduction in admission was observed also for patients with heart failure, with a delta of −56% for the last period of observation in comparison with 2018 and 2019 (p < 0.0001), in agreement with data reported by Severino et al and demonstrating a reduction of admission during the lockdown (13). These findings suggest that the ubiquitous presence of COVID-19 news on the mass media and social media and the lack of verified information have contributed to the perception of unsafe hospitals, even if hospital were not overwhelmed by the COVID-19 emergency, as in Tuscany, and an underestimation of mortality and morbidity risks due to cardiac conditions.…”
Section: Discussionsupporting
confidence: 92%
“…In this study we extended the time frame of observation reporting the data of the first trimester 2020 from a different region of Italy, i.e., the Tuscany, and we demonstrated that a low rate of contacts to EMS during this pandemic was observed also in regions of Italy less affected by the pandemic. We found that the reduction in admission was observed also for patients with heart failure, with a delta of −56% for the last period of observation in comparison with 2018 and 2019 (p < 0.0001), in agreement with data reported by Severino et al and demonstrating a reduction of admission during the lockdown (13). These findings suggest that the ubiquitous presence of COVID-19 news on the mass media and social media and the lack of verified information have contributed to the perception of unsafe hospitals, even if hospital were not overwhelmed by the COVID-19 emergency, as in Tuscany, and an underestimation of mortality and morbidity risks due to cardiac conditions.…”
Section: Discussionsupporting
confidence: 92%
“…Perhaps more interesting is the current data suggesting a trend towards reduced hospital admissions for diagnoses other than COVID-19, including other cardiac conditions such as ACS and new-onset atrial fibrillation [3,5]. Early studies from Europe and the UK have described reductions in HF admission and readmissions during the COVID-19 pandemic [3,8,[12][13][14][15]. Currently, robust prospective and retrospective data regarding the impact of the COVID-19 pandemic on HF admission in the USA remain limited.…”
Section: Discussionmentioning
confidence: 99%
“…During the pandemic, the primary focus of many hospitals shifted, out of necessity, from a wide breadth of medical care to treating the morbidity and mortality of COVID-19 patients, with multiple studies demonstrating this phenomenon with decreased inpatient admissions for non-COVID-19-related problems, including asthma, atrial fibrillation, acute Coronary Syndrome (ACS), and influenza [3][4][5][6][7]. The COVID-19 pandemic has been shown to similarly impact hospital admissions for heart failure (HF), with the most robust data originating from major tertiary centers in Europe and the UK [7,8]. Data on the COVID-19 pandemic's impact on US HF admissions remains Savalan Babapoor-Farrokhran and Jafar Alzubi contributed equally to this work.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, epidemiological findings from countries with low COVID-19 incidence during the first wave of the pandemic, including Greece, were comparable [ 4 ]. During this same period, in Norway, a 29% reduction in the weekly number of admissions for stroke and 41% for transient ischemic attack during the 1st 7 weeks of the pandemic lockdown were observed [ 5 ], while admissions for heart failure in Italy were reduced by 70% [ 6 ]. In the USA alone, there was an overall 42.8% reduction in admissions, varying from 23.7% for pancreatitis to 68.6% for chronic obstructive pulmonary disease (COPD)/asthma [ 7 ].…”
Section: Introductionmentioning
confidence: 99%